The Influence of Brand Image, Product Innovation, and Marketing Content on Purchasing Decisions Honda Scoopy Motorbikes in Denpasar City - Agustina, Febyola; Widnyani, Ni Made; Richadinata, Kadek Riyan Putra (West Science Interdisciplinary Studies, 2024)
Changes in consumer preferences in the motorcycle industry demand companies to enchance their marketing strategies to meet the need for efficient transportation amidst intense market competition. Denpasar serves as a prominent commercial hub, facilitating the acquisition of information. This research carried out in Denpasar, a city divided into four districts, with the objective of evaluating the impact of brand image, product development, and marketing content on the purchasing decisions for Honda Scoopy scooters in the region. A quantitative, descriptive research approach was employed. The target population included motorcycle riders who did not currently own a Honda Scoopy. A purposive sampling method was utilized, resulting in a sample 100 respondents. Data were collected using a structured survey consisting of 18 questions designed to measure each variable. The responses from the 100 participants were analyzed using multiple regression analysis with SPSS Statistics 26. The results indicate that brand image substantial impacts on consumer decision-making. Marketing content also affects these decisions, while product innovation has a substantial and positive effect on purchasing choices. The coefficient of determination (R²) is 73.4%, suggesting that brand image, product innovation, and marketing content collectively explain 73.4% of the variance in purchasing decisions. Factors that are not included in the regression model have an impact on the remaining 26.6%. Therefore, can surmised that brand image, product development, and marketing content significantly impact purchasing decisions.